Learning Arabic using telegram in the laptop : The language learning style of Malaysian gifted learners - KAMIS, M.S.; ALIAS, M.N.; LUBIS, M.A.; Damien, Mikeng; ABIDIN, S.G.Z.; ISMAIL, M.J.; YUSOF, R. (Journal of Language and Linguistic Studies, 2021)
This study is related to learning styles and technology; for example, the use of telegram in the laptop among Malaysian Gifted Learners (MGL) at Pusat GENIUS@Pintar Negara, UKM. This study aims to investigate the three research questions. The first research question, what is the visual level of Arabic language learning- style using telegram in the laptop among MGL? Secondly, what is the auditory -level of Arabic language learning style using telegram in the laptop among MGL? And Thirdly,what is the kinaesthetic-level of Arabic language learning-style using telegram in the laptop among MGL? The results of the finding indicate the MGLs are a high-level user of visual and kinaesthetic learning styles. As for the auditory-level, they are at a moderate level.This study suggests that MGLs can increase their creativity of learning when they focus on their most exciting subject if teachers can teach MGLs’ subject related to technology that includes visual and kinaesthetic.